Case series of cranial and spinal dysraphism - Gayathri Pandurangam; D Nagajyothi; Seethamsetty Saritha; Asra Anjum (Wolters Kluwer Medknow Publications, 2022)
Neural tube defects (NTDs) are the second most common cause of congenital anomaly worldwide (cardiac anomalies is the first). The 3rd and 4th week of gestation is the critical period for neural tube development. Multiple genetic and environmental factors are known to cause the NTDs in a developing embryo. We report here four cases of cranial and spinal dysraphism or craniorachischisis, the most severe and rare type of NTD with brief maternal history. In all these cases, the neural tissue is exposed in the region of brain as well as in the region of spinal cord to various extents. In this case series, the external features of craniorachischisis in four female fetuses (including monozygotic twins) are reported. One of the affected fetuses had associated omphalocele.